Predicting depressive symptom by cardiometabolic indicators in mid-aged and older adults in China: a population-based cross-sectional study - Wang, Ying; Zhang, Xiaoyun; Li, Yuqing; Gui, Jiaofeng; Mei, Yujin; Yang, Xue; Liu, Haiyang; Guo, Lei-lei; Li, Jinlong; Lei, Yunxiao; Li, Xiaoping; Sun, Lu; et al. (Frontiers in Psychiatry, 2023)
Depression is a serious mental illness often accompanied by physical and emotional problems. The prevalence of depressive symptoms in older adults has become an increasingly important public health priority. This study used indicators related to obesity and blood lipids to predict depressive symptoms in middle-aged and elderly Chinese.